Toxins - Ladant, Daniel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Toxins are biologically active substances produced by most kinds of living organisms, bacteria, fungi, plants, and animals. They present a vast diversity of molecular structures and target a wide variety of receptors involved in a range of physiological processes. As toxins are selected during evolution to acquire/improve their disabling/lethal effects, they display finely tuned functional properties often associated with high affinities and selectivity. Moreover, toxins are valuable tools to unravel cellular processes due to their extreme specificity for cell surface and/or intracellular targets. Therefore, toxins are very attractive compounds because of their Janus-like character; while they mostly act as deadly poisons like monstrous Mr. Hyde, they can also be tamed into good remedies like admirable Dr. Jekyll. As such, they have been primarily investigated not only for the light they can throw on fundamental physiological processes but also for their potential therapeutic applications. This reprint, emerging from the 27th Annual Meeting of the French Society of Toxinology (SFET, http://sfet.asso.fr/international), will be of great interest for those in the scientific community who want to know more about the fascinating world of toxins.